2014
DOI: 10.1371/journal.pone.0113923
|View full text |Cite
|
Sign up to set email alerts
|

The Repeat Region of the Circumsporozoite Protein is Critical for Sporozoite Formation and Maturation in Plasmodium

Abstract: The circumsporozoite protein (CSP) is the major surface protein of the sporozoite stage of malaria parasites and has multiple functions as the parasite develops and then migrates from the mosquito midgut to the mammalian liver. The overall structure of CSP is conserved among Plasmodium species, consisting of a species-specific central tandem repeat region flanked by two conserved domains: the NH2-terminus and the thrombospondin repeat (TSR) at the COOH-terminus. Although the central repeat region is an immunod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
59
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 43 publications
(63 citation statements)
references
References 34 publications
4
59
0
Order By: Relevance
“…Ultrastructure analysis of oocyst development revealed an enlarged nucleus that formed a large multiple lobed structure with multiple nuclear poles, followed by formation of large numbers of sporozoites at the plasmalemma of the oocyst (Fig. 5Bi), as described previously (Ferguson et al, 2014;Schrevel et al, 1977). Detailed examination showed nuclear poles with kinetochores directed toward the developing sporozoites ( Fig.…”
Section: Rapid Spindle Dynamics and Ndc80-gfp Localisation During Endsupporting
confidence: 66%
“…Ultrastructure analysis of oocyst development revealed an enlarged nucleus that formed a large multiple lobed structure with multiple nuclear poles, followed by formation of large numbers of sporozoites at the plasmalemma of the oocyst (Fig. 5Bi), as described previously (Ferguson et al, 2014;Schrevel et al, 1977). Detailed examination showed nuclear poles with kinetochores directed toward the developing sporozoites ( Fig.…”
Section: Rapid Spindle Dynamics and Ndc80-gfp Localisation During Endsupporting
confidence: 66%
“…However, removal of the repetitive regions of other proteins can affect activity; deletion of repeat regions of the parasite circumsporozoite protein and ring-exported protein 1 (REX1) lead to loss of protein function (36, 37). The knob-associated histidine-rich protein (KAHRP) is involved in both rigidifying the host cell (23) and the formation of cytoadherent knob structures (16), and deletion of a C-terminal sequence encompassing two lysine-rich repetitive sequences results in smaller knob structures and reduced cytoadhesion (38).…”
Section: Introductionmentioning
confidence: 99%
“…Gene knock-out studies in P. falciparum have demonstrated that CSP is required for the structural development of sporozoites (16). A recent study demonstrated that the repeat region is also critically required for sporozoite formation and maturation (17). Other than the structural requirement of CSP for sporozoites, in the human host, it is functionally involved in hepatocyte invasion by the parasite, as antibodies directed against CSP prevented sporozoite invasion into hepatocytes (18 -20).…”
mentioning
confidence: 99%